2007
DOI: 10.21829/azm.2007.232572
|View full text |Cite
|
Sign up to set email alerts
|

Descripción de los estados inmaduros de Astaena valida (Coleoptera: Melolonthidae: Melolonthinae: Sericini)

Abstract: RESUMENLas larvas y adultos de varias especies de Astaena dañan las raíces y el follaje de cultivos en climas templados y fríos en Colombia. En el presente artículo se describen la larva de tercer estadio y la pupa de macho y hembra de Astaena valida Burm., se ilustran sus caracteres diagnósticos y se propone una clave para distinguir sus larvas de otros Melolonthinae locales. Se confirmó que las larvas son rizófagas, y se encuentran en grupos de hasta 36 ejemplares/m 2 , prosperan en suelos disfuncionales, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
1
14
0
2
Order By: Relevance
“…Upon reaching the adult phase they weighed 101.0 mg on average (n = 25). Pardo-Locarno et al (2006) reported that third instar larvae of L. femoratus varied in length from 18 to 21 mm and in width from 4 to 5 mm, and width of the head capsules ranged from 3 to 3.2 mm. Puker et al (2009) found that adults of L. dorsalis measured on average 10.5 mm long by 4.6 mm wide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reaching the adult phase they weighed 101.0 mg on average (n = 25). Pardo-Locarno et al (2006) reported that third instar larvae of L. femoratus varied in length from 18 to 21 mm and in width from 4 to 5 mm, and width of the head capsules ranged from 3 to 3.2 mm. Puker et al (2009) found that adults of L. dorsalis measured on average 10.5 mm long by 4.6 mm wide.…”
Section: Resultsmentioning
confidence: 99%
“…as pests of the roots of plants in agroecological systems. Pardo-Locarno et al (2006) reported Leucothyreus femoratus Burmeister, 1844, in Colombia, as agriculturally important, both in their larval and adult phases.…”
mentioning
confidence: 99%
“…Além do comprimento e largura, o peso das pupas fêmeas também foi superior ao dos machos, que pesaram respectivamente 189,9 e 141,1 mg e possuíam coloração amarela (Tabela II). As pupas dos machos de L. femoratus possuem corpo ovalado, robusto, coloração amarelo claro e medem cerca de 14 a 16 mm de comprimento por 7 a 12 mm de largura (Pardo-Locarno et al 2006).…”
Section: Resultsunclassified
“…Although Ohaus (1900) recorded female pupae of Geniates barbatus and G. castaneus Burmeister, 1844, about 50 cm deep in the soil, their immature stages remain undescribed. In fact, the immature of only one species of Geniatini is known: Leucothyreus femoratus Burmeister, 1844, described by Pardo-Locarno et al (2006). Therefore the description of the larva and pupa of Geniates presented here represents an important addition to the knowledge of the immatures of Sacarabaeidae and to the taxonomy of Rutelinae.…”
mentioning
confidence: 80%
“…Pardo-Locarno et al (2006) proposed the separation between Geniatini (based on L. femoratus) and Anoplognatini (based on two species of Platycoelia Dejean, 1833, the single genus with described larvae in Anoplognathini; see Paucar-Cabrera & Smith 2002) using maxillary and palidial characters, as follows: Geniatini have lacinia with two unci and the maxillary stridulatory organ formed by heterogeneous teeth; meanwhile Anoplognathini have lacinia with three unci and homogeneous teeth in the maxillary stridulatory organ. Regarding these characters, the larvae of G. barbatus resemble more the larvae of Platycoelia than the larvae of L. femoratus.…”
Section: Key To the Third Instar Larvae Of Neotropicalmentioning
confidence: 99%